A method for preparing irradiated metal micro-nanomechanical samples

By performing ion irradiation and grain orientation marking on metal block materials and preparing in situ mechanical samples in combination with focusing ion beam technology, the problem of difficulty in preparing in situ mechanical samples of irradiated metal samples in the same grain in the prior art is solved, and efficient and low-cost mechanical data characterization and analysis are achieved.

CN119309897BActive Publication Date: 2025-03-25XI AN JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411854693.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-25
Estimated Expiration
2044-12-17

AI Technical Summary

Technical Problem

The prior art cannot directly prepare in-situ mechanical samples for irradiated metal samples in the same grain, making it difficult to objectively compare the mechanical data before and after irradiation of metal samples and their accuracy of normalization, and is cost-effective and inefficient.

Method used

By providing the metal block material for ion irradiation, the grain orientation is determined and the focused ion beam electron microscope is performed. Then, the original rectangular sheet sample is prepared using the focused ion beam, and some irradiation layer is removed and trimmed on its surface to form an irradiation and unirradiated area under the same grain orientation, and finally thinning is performed to obtain a micro-nano mechanical sample.

Benefits of technology

In situ mechanical samples of irradiated and unirradiated single crystals in situ are achieved in the same grain of the metal block sample after irradiation, reducing the preparation cost, improving efficiency, and enhancing the characterization accuracy of irradiated hardening performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119309897B_ABST
    Figure CN119309897B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of metal material preparation, and specifically relates to a method for preparing irradiated metal micro-nanomechanical samples. The method comprises the following steps: providing a metal bulk material, ion irradiating the metal bulk material to obtain an initial sample; fixing the initial sample, determining the grain orientation and marking the oriented grains of the initial sample, and preparing the sample to obtain an original rectangular thin sheet sample; removing part of the irradiated layer from the surface of the original rectangular thin sheet sample and trimming it to obtain an irradiated area and a non-irradiated area under the same grain orientation, and a crenel-shaped rough blank with a continuous concave-convex structure; thinning to obtain a micro-nanomechanical sample. The present invention obtains irradiated and non-irradiated single crystal in-situ mechanical samples with the same orientation in the same grain of the irradiated metal bulk sample, avoids searching for the same orientation irradiated area and non-irradiated area in multiple samples, reduces the analysis error caused by collecting data in different areas, and thus realizes the efficient preparation of single crystal in-situ mechanical samples under transmission electron microscopy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of metal material preparation, and in particular relates to a method for preparing irradiated metal micro-nanomechanical samples. Background Art

[0002] In recent years, with the rapid development of nuclear energy, equipment construction, deep space, deep sea exploration and other fields, there is an urgent need for the research and development of nuclear reactors. Nuclear reactor structural materials need to withstand high doses of particle irradiation, which will cause the ductile-brittle transition temperature to rise, resulting in serious irradiation embrittlement, endangering the safety of new reactors. Therefore, it is particularly important to study the changes in the mechanical properties of reactor materials and their candidate materials under high-energy particle bombardment.

[0003] At present, since the affected area of ​​most samples after ion irradiation is relatively shallow, it is difficult to test their mechanical properties through large-scale sample testing. In recent years, in-situ mechanical technology has gradually become one of the common paradigms for mechanical property testing and deformation behavior / failure mechanism research of micro-nanoscale materials, and using it to test the mechanical properties of samples subjected to ion irradiation is also a very effective way.

[0004] In-situ mechanical property testing of samples after ion irradiation requires in-situ mechanical sampling of irradiated and unirradiated areas under the same grain orientation. Traditional methods cannot directly sample irradiated and unirradiated areas within the same grain, which makes it difficult to objectively compare the mechanical data and the accuracy of normalization of metal samples before and after irradiation due to the composition uniformity of different grains. It is also costly and inefficient. Summary of the invention

[0005] The purpose of the present invention is to provide a method for preparing irradiated metal micro-nano mechanical samples, aiming to solve the shortcoming of the prior art that it is impossible to prepare in-situ mechanical specimens of irradiated metal samples in the same grain. The method is to prepare in-situ single crystal mechanical specimens in the irradiated area and the non-irradiated area of ​​the same grain of the metal sample with the same orientation. The method has the characteristics of low production cost, simple operation process and high efficiency, and realizes the accurate characterization and objective analysis of the mechanical data of the metal sample before and after irradiation.

[0006] The present invention solves the above technical problems through the following technical solutions.

[0007] The object of the present invention is to provide a method for preparing a metal micro-nanomechanical sample after irradiation, comprising the following steps:

[0008] A metal bulk material is provided, and ion irradiation is performed on the metal bulk material to obtain an initial sample.

[0009] The initial sample is fixed, and the grain orientation of the initial sample is determined by electron backscatter diffractometer, and the oriented grains are marked by focused ion beam electron microscope. After the grains are marked, the marked grains are sampled by focused ion beam to obtain the original rectangular thin slice sample.

[0010] The copper mesh is fixed and rotated until the copper mesh and the focused ion beam are perpendicular, and then the original rectangular thin film sample is pasted on the copper mesh. Part of the irradiated layer on the surface of the original rectangular thin film sample is removed and trimmed to obtain the irradiated area and the non-irradiated area under the same grain orientation, forming a crenel-shaped rough blank with a continuous concave-convex structure; the crenel-shaped rough blank is thinned so that the convexities in the crenel-shaped rough blank form an in-situ mechanical column sample to obtain a micro-nano mechanical sample.

[0011] Furthermore, the height-to-diameter ratio of the in-situ mechanical column specimen is 2 to 3: 1. It should be noted that a cylindrical specimen with a height-to-diameter ratio that is too high or too low cannot fully reflect the mechanical properties of the material. A high height-to-diameter ratio is more likely to cause bending during in-situ compression, while a low height-to-diameter ratio may cause stress concentration on the edge and contact surface of the sample.

[0012] Furthermore, when removing part of the irradiated layer, the copper mesh is rotated horizontally by 180° and then vertically by 7°, so that the copper mesh and the focused ion beam are perpendicular, and then the original rectangular thin film sample is pasted on the copper mesh, and the focused ion beam is used to remove part of the irradiated layer. The voltage of the focused ion beam is 30 kV, and the current is 0.79 nA to 2.6 nA, and the irradiated area and the unirradiated area under the same grain orientation are obtained. Among them, the irradiated layer is removed from the surface of the original rectangular thin film sample, and the thickness of the removed sample is about 1.5 to 2 times the ion irradiation depth. The voltage of the focused ion beam is 30 kV, and the current is 0.79 nA to 2.6 nA; when trimming, the voltage of the focused ion beam is 30 kV, and the current is 2.6 nA. Removing part of the irradiated layer and trimming are to remove and trim the area marked by the oriented grains, but not completely remove it. Only part of the irradiated layer is removed to form the irradiated area and the unirradiated area. The range of removing the irradiated layer is not fixed, and the removal range can be determined according to actual needs.

[0013] Furthermore, during trimming, the interval between adjacent convex shapes in the crenel-shaped rough blank is 2.5 μm to 3 μm, and the initial width of each convex shape is 1.5 μm to 2 μm. Among them, the convex structure is an in-situ mechanical column rough blank, that is, the initial width of the in-situ mechanical column rough blank is 1.5 μm to 2 μm, the purpose is to leave enough margin to facilitate the acquisition of in-situ mechanical columns of different size requirements during thinning; and the interval between two adjacent in-situ mechanical column rough blanks is 2.5 μm to 3 μm, the purpose is to ensure that when conducting an in-situ mechanical experiment on a certain column, adjacent in-situ mechanical columns are prevented from being accidentally hit by the indenter.

[0014] Furthermore, when determining the grain orientation of the initial sample, the initial sample is glued to the sample stage, and then the detector in the electron backscatter diffractometer is used to determine the grain orientation of the sample. The voltage of the detector to determine the grain orientation is 20 kV, and the current is 13 nA to 26 nA; when the focused ion beam electron microscope is used to mark the oriented grains, the voltage of the focused ion beam is 30 kV and the current is 0.26 nA. The orientation of the grain sample is determined by the detector in the electron backscatter diffractometer, mainly to facilitate the selection of a specific orientation in the subsequent in-situ mechanical sample preparation. The purpose of grain marking is to find specific grains more quickly after replacing the sample stage.

[0015] Furthermore, when the focused ion beam is used for sample preparation, a U-shaped pit is used for the marked grains, wherein the voltage of the focused ion beam is 30 kV, the current is 9.9 nA to 22 nA, and after the U-shaped pit is cut, the length of the upper pit is 30 μm to 50 μm, the width of the upper pit is 12 μm to 15 μm, and the height of the upper pit is 10 μm to 15 μm; the length of the lower pit is 30 μm to 50 μm, the width of the lower pit is 13 μm to 15 μm, and the height of the lower pit is 10 μm to 15 μm. The purpose of selecting the size of the U-shaped pit is to prepare multiple in-situ mechanical columns in the irradiated area and the non-irradiated area of ​​the same sample, and the purpose of conducting multiple in-situ mechanical experiments is to improve the repeatability of the experiment, thereby enhancing the reliability of the experimental data. It can effectively reduce the random errors and contingency in the data, and realize the accurate characterization and objective analysis of the mechanical data of metal samples before and after irradiation.

[0016] Furthermore, the original rectangular thin-sheet sample has a length of 30 μm to 50 μm, a width of 1.5 μm to 2 μm, and a height of 7 μm to 9 μm.

[0017] Furthermore, the thinning is annular thinning in the cleaning mode; during thinning, the rough blank is thinned so that the outer diameter of the convex structure in the crenel-shaped rough blank is reduced from 3.5 μm to 0.6 μm, the inner diameter is reduced from 1.5 μm to 0.5 μm, and the depth is 0.05 μm; the thinning method is thinning from the outside to the inside; the thinning voltage is 30 kV, and the current is 26 pA to 41 pA. Among them, the decreasing method is to gradually reduce the size by 0.2 μm each time until the target size.

[0018] Furthermore, the specific method of pasting the original rectangular thin film sample on the copper mesh is: under an optical microscope, the copper mesh is pasted parallel to the sample holder, and then the sample holder containing the copper mesh is fixed on the sample stage, and in the focused ion beam electron microscope, the sample stage is rotated horizontally 180° and then vertically 45°, the purpose is to make the top of the copper mesh perpendicular to the electron beam, that is, to stick the sample to the copper mesh, and then paste the original rectangular thin film sample on the copper mesh.

[0019] Furthermore, during the preparation of the irradiated samples, sandpaper with a mesh size of 400 to 4000 was used to remove the oxide layer on the surface of the metal sample, and then vibration polishing was performed to remove the surface stress of the metal sample.

[0020] Furthermore, the obtained micro-nanomechanical samples are in-situ single crystal columnar samples used for in-situ mechanical testing using a transmission electron microscope.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The present invention proposes a method for preparing irradiated metal micro-nano mechanical samples by using focused ion beam technology. The method is based on samples of ion irradiated metal bulk materials. After determining the grain orientation and marking the grains by a focused ion beam electron microscope, the marked grains are sampled by using a focused ion beam to obtain an original rectangular thin slice sample. A part of the irradiated layer on the surface of the original rectangular thin slice sample is removed and trimmed to obtain an irradiated area and a non-irradiated area under the same grain orientation. The micro-nano mechanical sample is then obtained after thinning. In the same grain of the irradiated metal bulk sample, irradiated and non-irradiated single crystal in-situ mechanical samples with the same orientation can be obtained, avoiding the search for irradiated areas and non-irradiated areas with the same orientation in multiple samples, reducing the analysis error caused by collecting data in different areas, thereby realizing high-efficiency preparation of transmission electron microscope single crystal in-situ mechanical samples and improving the characterization accuracy of the radiation hardening performance of metals after ion irradiation. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a sample diagram of the original rectangular thin slice obtained in Example 1 of the present invention.

[0024] Figure 2 This is a picture of the original rectangular thin sheet sample obtained in Example 1 of the present invention pasted on the top of the copper mesh.

[0025] Figure 3 This is a rough image of the crenel-shaped continuous concave-convex structure obtained in Example 1 of the present invention.

[0026] Figure 4 This is the in-situ mechanical sample diagram of the irradiated area obtained in Example 1 of the present invention.

[0027] Figure 5 This is the in-situ mechanical sample diagram of the non-irradiated area obtained in Example 1 of the present invention.

[0028] Figure 6 This is a stress-strain curve diagram of the non-irradiated area sample obtained in Example 1 of the present invention.

[0029] Figure 7 This is a stress-strain curve diagram of the irradiated area sample obtained in Example 1 of the present invention.

[0030] Figure 8 This is a stress-strain curve diagram of the irradiated area sample obtained in Example 2 of the present invention.

[0031] Fig. 9 This is a stress-strain curve diagram of the irradiated area sample obtained in Example 3 of the present invention. DETAILED DESCRIPTION

[0032] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Certain words are used in the present invention to refer to specific components. It should be understood by those skilled in the art that technicians will use different nouns to refer to the same component. The present invention does not distinguish the components by the difference in nouns, but by the difference in functions of the components.

[0034] In-situ mechanical property testing of samples after ion irradiation requires in-situ mechanical sampling of irradiated and unirradiated areas under the same grain orientation. Traditional methods cannot directly sample irradiated and unirradiated areas within the same grain, which makes it difficult to objectively compare the mechanical data and the accuracy of normalization of metal samples before and after irradiation due to the composition uniformity of different grains. It is also costly and inefficient.

[0035] Based on the above problems, the present invention provides a method for preparing irradiated metal micro-nanomechanical samples, comprising the following steps:

[0036] S1. Provide a metal bulk material, and perform ion irradiation on the metal bulk material to obtain an initial sample.

[0037] S2. Fix the initial sample on the sample stage, use an electron backscatter diffractometer to determine the grain orientation of the initial sample, and use a focused ion beam electron microscope to mark the oriented grains. The abbreviation of focused ion beam is FIB, and its full English name is Focused Ion Beam.

[0038] S3. After the grains are marked, the marked grains are sampled using a focused ion beam to obtain the original rectangular thin slice specimen.

[0039] S4. Fix the copper mesh on the sample stage through the sample holder, rotate the copper mesh until it is perpendicular to the focused ion beam, use the ion beam to trim the copper mesh until it is level with the sample holder, and stick the original rectangular thin slice sample on the copper mesh.

[0040] S5. Then, when the sample stage is tilted at a 7° angle, part of the irradiated layer is removed from the surface of the original rectangular thin slice sample and trimmed to obtain irradiated areas and non-irradiated areas with the same grain orientation, forming a crenel-shaped rough blank with a continuous concave-convex structure.

[0041] S6. Thinning the crenel-shaped rough blank with a continuous concave-convex structure so that the convex shapes in the crenel-shaped rough blank form an in-situ mechanical column specimen to obtain a micro-nano mechanical sample.

[0042] The present invention solves the shortcoming of the prior art that in-situ mechanical specimens of irradiated metal samples cannot be prepared in the same grain. Based on the sample of ion irradiated metal bulk material, after determining the grain orientation and marking the grains by focused ion beam electron microscope, the marked grains are sampled by focused ion beam to obtain the original rectangular thin slice sample, and a part of the irradiated layer on the surface of the original rectangular thin slice sample is removed and trimmed to obtain the irradiated area and the non-irradiated area under the same grain orientation, and then thinned to obtain the micro-nano mechanical sample. In the same grain of the irradiated metal bulk sample, irradiated and non-irradiated single crystal in-situ mechanical samples with the same orientation can be obtained, avoiding the search for the irradiated area and the non-irradiated area with the same orientation in multiple samples, reducing the analysis error caused by collecting data in different areas, thereby realizing high-efficiency preparation of single crystal in-situ mechanical samples and improving the characterization accuracy of the radiation hardening performance of metal after ion irradiation.

[0043] The invention is further described below through specific examples.

[0044] Example 1

[0045] A method for preparing irradiated metal micro-nanomechanical samples using zirconium alloy, using the zirconium alloy irradiated with argon ions as a model material, comprising the following steps:

[0046] S1. Provide a zirconium alloy block material with a length, width and height of 10 mm*5 mm*1.5 mm. Use 400 mesh, 1000 mesh, 2500 mesh and 4000 mesh sandpaper to remove the oxide layer on the surface of the metal block sample in turn; then use alumina polishing liquid to polish for about 10 min; then polish the sample on a vibration polishing machine to achieve the effect of removing the surface stress of the sample; finally, the block sample after polishing is cleaned twice, acetone cleaning for 10 min and alcohol cleaning for 10 min, to remove stains and polishing agents on the sample surface. Then, according to the zirconium alloy material, an argon ion source is injected, and the zirconium alloy material is irradiated with 1.8 MeV argon ions at a temperature of 300 °C to obtain an initial sample.

[0047] S2. The initial sample is bonded to a height-adjustable multi-purpose sample stage with double-sided copper glue, and the grain orientation of the initial sample is determined by the detector of the electron backscatter diffractometer. When determining the grain orientation, the detector orientation parameters are: voltage is 20 kV, current is 26 nA; and the focused ion beam electron microscope is used for marking. When the focused ion beam electron microscope is used to mark the oriented grains: voltage is 30 kV, current is 0.26 nA, and the selected orientation is

[0001] .

[0048] S3. Replace the height-adjustable multi-purpose sample stage with a 38° pre-tilted sample stage, and perform conventional transmission electron microscope sample preparation, that is, perform U-shaped cutting and digging of the marked grains on the 38° pre-tilted sample stage. The voltage and current selected for digging are 30 kV and 9.9 nA, the length of the upper pit is 40 μm, the width of the upper pit is 12 μm, and the height of the upper pit is 10 μm; the length of the lower pit is 40 μm, the width of the lower pit is 15 μm, and the height of the lower pit is 10 μm. Fine trimming is performed. It should be noted that due to the large size of the sample, a "U-shaped cut" needs to be performed on both sides of the sample when performing the "U-shaped cut", and finally the original rectangular thin slice sample is obtained. Figure 1 This is a sample diagram of the original rectangular thin slice obtained in Example 1 of the present invention, as shown in Figure 1 As shown, the original rectangular thin film sample has a length of 35 μm, a width of 1.5 μm, and a height of 8 μm, and is pasted on the nanohand with Pt.

[0049] S4. Heat the sample holder to 150 °C under an optical microscope, then evenly apply hot melt adhesive on the sample holder. Then place the copper mesh on the sample holder at this temperature and adjust the position until they are level with each other. Finally, cool it down and install it on the threaded clamping table.

[0050] S5. Replace the 38° pre-tilted sample stage with a height-adjustable multi-purpose sample stage, glue the threaded clamping stage to the sample stage, and then rotate the sample stage horizontally 180° and vertically 7°. Observe the direction of the copper mesh and the in-situ mechanical sample holder under the ion beam, and then use the ion beam to trim them to the same level, and glue the sample to the copper mesh. Figure 2 As shown, Figure 2 This is a diagram of the original rectangular thin sheet sample obtained in Example 1 of the present invention being pasted on the top of the copper mesh.

[0051] S6. When the height-adjustable multi-purpose sample stage is at an angle of 7°, the irradiated layer of the sample is cut off. When the irradiated layer is cut off, the voltage of the focused ion beam is 30 kV, the current is 2.6 nA, the size of the cut irradiated layer is 1.5 μm, and it is trimmed. When trimming, the initial width of each convex shape in the crenel-shaped rough blank of the continuous concave-convex structure is 1.5 μm, and the interval between adjacent convex shapes is 2.5 μm, that is, the initial width of the in-situ mechanical column rough blank is 1.5 μm, and the interval between two adjacent in-situ mechanical column rough blanks is 2.5 μm. When trimming, the voltage of the focused ion beam is 30 kV, and the current is 2.6 nA; the irradiated area and the non-irradiated area under the same grain orientation are obtained, forming a crenel-shaped rough blank with a continuous concave-convex structure; Figure 3 The crenel-shaped rough blank image of the continuous concave-convex structure obtained in Example 1 of the present invention is as follows: Figure 3 As shown, Figure 3 In the figure, the area ①-⑤ is the irradiated area, and the area ⑥-⑨ is the area where the irradiated layer is cut off, that is, the non-irradiated area.

[0052] S7. On the basis of the above, the sample stage was rotated horizontally 180° to the initial angle, and then vertically rotated 7° to thin the sample. The thinning mode was the cleaning mode. The thinning tool was an annular thinning tool. The outer diameter was gradually reduced from 3.5 μm to 0.6 μm by 0.2 μm at a time, and the inner diameter was gradually reduced from 1.5 μm to 0.5 μm by 0.2 μm at a time. The depth value was 0.05 μm. The thinning method was gradual thinning from the outside to the inside. The voltage during thinning was 30 kV and the current was 41pA.

[0053] S8. A micro-nanomechanical sample is obtained, in which the height-to-diameter ratio of the in-situ mechanical cylindrical specimen is about 3:1. Figure 4 This is the in-situ mechanical sample diagram of the irradiated area obtained in Example 1 of the present invention. Figure 5 This is the in-situ mechanical sample diagram of the non-irradiated area obtained in Example 1 of the present invention. Figure 4 and Figure 5 As shown, irradiated and non-irradiated single crystal in-situ mechanical samples with the same orientation can be obtained within the same grain of the irradiated metal bulk sample.

[0054] Example 2

[0055] A method for preparing irradiated metal micro-nanomechanical samples using NbZrTi-based high entropy alloys, using NbZrTi irradiated with gold ions as a model material, comprising the following steps:

[0056] S1. Provide a piece of NbZrTi bulk material with a length, width and height of 5 mm*2.5 mm*1.5 mm. Use 400 mesh, 1000 mesh, 2500 mesh and 4000 mesh sandpaper to remove the oxide layer on the surface of the metal block sample in turn; then use alumina polishing liquid to polish for about 10 min; then polish the sample on a vibration polishing machine to achieve the effect of removing the surface stress of the sample; finally, the block sample after polishing is cleaned twice, acetone cleaning for 10 min and alcohol cleaning for 10 min, to remove stains and polishing agents on the sample surface. Then, according to the material selection, a gold ion source is injected, and the NbZrTi alloy material is irradiated with 6 MeV Au ions at a temperature of 400°C to obtain an initial sample.

[0057] S2. The initial sample was bonded to a height-adjustable multi-purpose sample stage with double-sided copper adhesive. The grain orientation of the initial sample was determined using the detector in the electron backscatter diffractometer. When determining the grain orientation, the detector orientation parameters were: voltage 30 kV, current 26 nA; and the focused ion beam electron microscope was used to mark the oriented grains. When the focused ion beam electron microscope was used to mark the oriented grains, the voltage was 30 kV and the current was 0.26 nA. The selected orientation was

[110] .

[0058] S3. Replace the height-adjustable multi-purpose sample stage with a 38° pre-tilted sample stage, and perform conventional transmission electron microscopy sample preparation, that is, perform U-shaped cutting and digging of the marked grains on the 38° pre-tilted sample stage. The voltage and current selected for digging are 30 kV and 9.9 nA, the length of the upper pit is 30 μm, the width of the upper pit is 12 μm, and the height of the upper pit is 10 μm; the length of the lower pit is 30 μm, the width of the lower pit is 15 μm, and the height of the lower pit is 10 μm, and then fine-tune it. It should be noted that due to the large size of the sample, a "U-shaped cut" needs to be performed on both sides of the sample when performing the "U-shaped cut". Finally, the original rectangular thin film sample is obtained. The original rectangular thin film sample is 20 μm long, 1.5 μm wide, and 8 μm high, and it is pasted on the nanohand with Pt.

[0059] S4. Heat the sample holder to 150°C under an optical microscope, then evenly apply hot melt adhesive on the sample holder. Then place the copper mesh on the sample holder at this temperature and adjust the position until they are level with each other. Finally, cool it and install it on the threaded clamping table.

[0060] S5. Replace the 38° pre-tilted sample stage with a height-adjustable multi-purpose sample stage, glue the threaded clamping table to the sample stage, then rotate the sample stage horizontally 180° and vertically 7°, observe the direction of the copper mesh and the in-situ mechanical sample holder under the ion beam, then use the ion beam to trim them until they are level, and glue the sample to the copper mesh.

[0061] S6. When the angle of the height-adjustable multi-purpose sample stage is 7°, the irradiated layer of the sample is cut off. When cutting off the irradiated layer, the voltage of the focused ion beam is 30 kV, the current is 2.6 nA, the size of the cut irradiated layer is 2.5 μm, and it is trimmed. When trimming, the initial width of each convexity in the crenel-shaped rough blank of the continuous concave-convex structure is 1.5 μm, and the interval between adjacent convexities is 3 μm, that is, the initial width of the in-situ mechanical column rough blank is 1.5 μm, and the interval between two adjacent in-situ mechanical column rough blanks is 3 μm. When trimming, the voltage of the focused ion beam is 30 kV, and the current is 2.6 nA. The irradiated area and the non-irradiated area under the same grain orientation are obtained to form a crenel-shaped rough blank with a continuous concave-convex structure.

[0062] S7. On the basis of the above, the sample stage was rotated horizontally 180° to the initial angle, and then vertically rotated 7° to thin the sample. The thinning mode was the cleaning mode. The thinning tool was an annular thinning tool. The outer diameter was gradually reduced from 3.5 μm to 0.6 μm by 0.2 μm at a time, and the inner diameter was gradually reduced from 1.5 μm to 0.5 μm by 0.2 μm at a time. The depth value was 0.05 μm. The thinning method was gradual thinning from the outside to the inside. The voltage during thinning was 30 kV and the current was 41pA.

[0063] S8. A micro-nanomechanical sample is obtained, wherein the height-to-diameter ratio of the in-situ mechanical cylindrical specimen in the micro-nanomechanical sample is about 2:1.

[0064] Example 3

[0065] A method for preparing irradiated metal micro-nanomechanical samples using zirconium alloy, using krypton ion irradiated zirconium alloy as a model material, comprising the following steps:

[0066] S1. Provide a piece of zirconium block material with a length, width and height of 5 mm*1.5 mm*1 mm. Use 400 mesh, 1000 mesh, 2500 mesh and 4000 mesh sandpaper to remove the oxide layer on the surface of the metal block sample in turn; then use alumina polishing liquid to polish for about 10 min; then polish the sample on a vibration polishing machine to achieve the effect of removing the surface stress of the sample; finally, the block sample after polishing is cleaned twice, acetone cleaning for 10 min and alcohol cleaning for 10 min, to remove stains and polishing agents on the sample surface. Then, according to the material selection, a krypton ion source is injected, and the zirconium alloy material is irradiated with 31 MeV Kr ions at a temperature of 350°C to obtain an initial sample.

[0067] S2. The initial sample was bonded to a height-adjustable multi-purpose sample stage with double-sided copper adhesive. The grain orientation of the initial sample was determined using the detector in the electron backscatter diffractometer. When determining the grain orientation, the detector orientation parameters were: voltage 20 kV, current 26 nA; and the focused ion beam electron microscope was used to mark the oriented grains. When the focused ion beam electron microscope was used to mark the oriented grains, the voltage was 30 kV and the current was 0.26 nA. The selected orientation was

[0001] .

[0068] S3. Replace the height-adjustable multi-purpose sample stage with a 38° pre-tilted sample stage, and perform conventional transmission electron microscopy sample preparation, that is, perform U-shaped cutting and digging of the marked grains on the 38° pre-tilted sample stage. The voltage and current selected for digging are 30 kV and 9.9 nA, the length of the upper pit is 40 μm, the width of the upper pit is 13 μm, and the height of the upper pit is 15 μm; the length of the lower pit is 40 μm, the width of the lower pit is 15 μm, and the height of the lower pit is 15 μm. Then, fine-tuning is performed. It should be noted that due to the large size of the sample, a "U-shaped cut" needs to be performed on both sides of the sample when performing the "U-shaped cut". Finally, the original rectangular thin slice sample is obtained. The original rectangular thin slice sample is 40 μm long, 1.8 μm wide, and 10 μm high, and it is pasted on the nanohand with Pt.

[0069] S4. Heat the sample holder to 150°C under an optical microscope, then evenly apply hot melt adhesive on the sample holder. Then place the copper mesh on the sample holder at this temperature and adjust the position until they are level with each other. Finally, cool it and install it on the threaded clamping table.

[0070] S5. Replace the 38° pre-tilted sample stage with a height-adjustable multi-purpose sample stage, glue the threaded clamping table to the sample stage, then rotate the sample stage horizontally 180° and vertically 7°, observe the direction of the copper mesh and the in-situ mechanical sample holder under the ion beam, then use the ion beam to trim them until they are level, and glue the sample to the copper mesh.

[0071] S6. When the angle of the height-adjustable multi-purpose sample stage is 7°, the irradiated layer of the sample is cut off. When cutting off the irradiated layer, the voltage of the focused ion beam is 30 kV, the current is 2.6 nA, the size of the cut irradiated layer is 4 μm, and it is trimmed. When trimming, the initial width of each convexity in the crenel-shaped rough blank of the continuous concave-convex structure is 2 μm, and the interval between adjacent convexities is 3 μm, that is, the initial width of the in-situ mechanical column rough blank is 2 μm, and the interval between two adjacent in-situ mechanical column rough blanks is 3 μm. When trimming, the voltage of the focused ion beam is 30 kV, and the current is 2.6 nA. The irradiated area and the non-irradiated area under the same grain orientation are obtained, forming a crenel-shaped rough blank with a continuous concave-convex structure.

[0072] S7. On the basis of the above, the sample stage was rotated horizontally 180° to the initial angle, and then vertically rotated 7° to thin the sample. The thinning mode was the cleaning mode. The thinning tool was an annular thinning tool. The outer diameter was gradually reduced from 3.5 μm to 0.6 μm by 0.2 μm at a time, and the inner diameter was gradually reduced from 1.5 μm to 0.5 μm by 0.2 μm at a time. The depth value was 0.05 μm. The thinning method was gradual thinning from the outside to the inside. The voltage during thinning was 30 kV and the current was 41pA.

[0073] S8. A micro-nanomechanical sample is obtained, wherein the height-to-diameter ratio of the in-situ mechanical cylindrical specimen in the micro-nanomechanical sample is about 2:1.

[0074] Figure 6 This is a stress-strain curve diagram of the non-irradiated area sample obtained in Example 1 of the present invention. Figure 7 : is a stress-strain curve of the irradiated area sample obtained in Example 1 of the present invention. Figure 6 and Figure 7 As shown, obvious radiation hardening phenomenon can be seen.

[0075] Figure 8 : is a stress-strain curve diagram of the irradiated area sample obtained in Example 2 of the present invention. Figure 8 As shown, its yield strength can be obtained and its radiation hardening can be further studied.

[0076] Fig. 9 3 is a stress-strain curve of the irradiated area sample obtained in Example 3 of the present invention. Fig. 9 As shown, its yield strength can be obtained and its radiation hardening can be further studied.

[0077] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0078] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing irradiated metal micro-nanomechanical samples, characterized in that: The following steps are involved: Providing a metal bulk material, and subjecting the metal bulk material to ion irradiation to obtain an initial sample; The initial sample is fixed, and the grain orientation of the initial sample is determined by electron backscatter diffractometer, and the oriented grains are marked by focused ion beam electron microscope. After the grains are marked, the marked grains are sampled by focused ion beam to obtain the original rectangular thin slice sample; When the focused ion beam is used for sample preparation, a U-shaped pit is cut and dug for the marked grains, wherein the voltage of the focused ion beam is 30 kV, the current is 9.9 nA to 22 nA, and after the U-shaped pit is cut and dug, the length of the upper pit is 30 μm to 50 μm, the width of the upper pit is 12 μm to 15 μm, and the height of the upper pit is 10 μm to 15 μm; the length of the lower pit is 30 μm to 50 μm, the width of the lower pit is 13 μm to 15 μm, and the height of the lower pit is 10 μm to 15 μm; The copper mesh is fixed and rotated until the copper mesh and the focused ion beam are perpendicular, and then the original rectangular thin slice sample is pasted on the copper mesh, and a part of the irradiated layer on the surface of the original rectangular thin slice sample is removed and trimmed to obtain the irradiated area and the non-irradiated area under the same grain orientation, forming a crenel-shaped rough blank with a continuous concave-convex structure; The rough blank is thinned so that the convex shapes in the crenel-shaped rough blank form in-situ mechanical column specimens to obtain micro-nano mechanical samples.

2. The method for preparing irradiated metal micro-nanomechanical samples according to claim 1, characterized in that: The height-to-diameter ratio of the in-situ mechanical column sample is 2-3:

1.

3. The method for preparing irradiated metal micro-nanomechanical samples according to claim 1, characterized in that: When removing part of the irradiated layer, the copper mesh was rotated horizontally 180° and then vertically 7° to make the copper mesh and the focused ion beam perpendicular. Then the original rectangular thin film sample was pasted on the copper mesh and part of the irradiated layer was removed using the focused ion beam. The voltage of the focused ion beam was 30 kV and the current was 0.79 nA to 2.6 nA to obtain the irradiated area and the non-irradiated area with the same grain orientation.

4. The method for preparing irradiated metal micro-nanomechanical samples according to claim 1, characterized in that: During trimming, the intervals between adjacent convexities in the crenel-shaped rough blank are 2.5 μm to 3 μm, and the initial width of each convexity is 1.5 μm to 2 μm.

5. The method for preparing irradiated metal micro-nanomechanical samples according to claim 1, characterized in that: When determining the grain orientation of the initial sample, the initial sample is glued to the sample stage, and then the detector in the electron backscatter diffractometer is used to determine the grain orientation of the sample. The voltage of the detector for determining the grain orientation is 20kV, and the current is 13nA~26nA; when the focused ion beam electron microscope marks the oriented grains, the voltage of the focused ion beam is 30kV and the current is 0.26nA.

6. The method for preparing irradiated metal micro-nanomechanical samples according to claim 1, characterized in that: The original rectangular thin slice sample has a length of 30 μm to 50 μm, a width of 1.5 μm to 2 μm, and a height of 7 μm to 9 μm.

7. The method for preparing irradiated metal micro-nanomechanical samples according to claim 1, characterized in that: The thinning method is annular thinning in a cleaning mode; during thinning, the rough blank is thinned so that the outer diameter of the convex structure in the crenel-shaped rough blank decreases from 3.5 μm to 0.6 μm, the inner diameter decreases from 1.5 μm to 0.5 μm, and the depth value is 0.05 μm; the thinning method is thinning from the outside to the inside; the thinning voltage is 30 kV, and the current is 26 pA to 41 pA.

8. The method for preparing irradiated metal micro-nanomechanical samples according to claim 1, characterized in that: The specific method of pasting the original rectangular thin film sample on the copper mesh is as follows: under an optical microscope, the copper mesh is pasted parallel to the sample holder, and then the sample holder containing the copper mesh is fixed on the sample stage. In the focused ion beam electron microscope, the sample stage is rotated horizontally 180° and then vertically 45°, and then the original rectangular thin film sample is pasted on the copper mesh.

9. The method for preparing irradiated metal micro-nanomechanical samples according to any one of claims 1 to 8, characterized in that: The prepared micro-nano mechanical samples are single crystal columnar samples used for in-situ mechanical testing under transmission electron microscopy.

Citation Information

Patent Citations

  • Transmission sample preparation method for processing irradiation block by using focused ion beam

    CN116399656A

  • KR20230034055A